Analysis of the Case of Divorce and Its Settlement in the Religious Court of Palu City - Rinalti Rinalti; Syahabuddin Syahabuddin; Ermawati Ermawati (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC LAW AND SOCIETY, 2020)
This paper discusses the cases of divorce and its settlement in the Religious Court of Palu. This study applied qualitative method with the data collection techniques that include observation, interview and written document. Data analysis was carried out through data reduction, presentation, verification and conclusion drawing. The result shows that the divorce proceedings handled by the Religious Court of Palu includes the applicants filed for divorce applications to the Religious Courts. Then, the Religious Courts make a number of lawsuit or application for divorce and file a summons. Furthermore, the panel of judges appointed a mediator to mediate between the litigating husband and wife. Conducting the first hearing with the agenda of reading the suit. The second hearing, listening to the response of the respondent or the defendant then delaying the decision. Listen to the testimonies of witnesses from each party. The panel of judges gives a decision on the case submitted and invites the respondent or the defendant to submit an appeal. The causes of divorce are adultery factors, drunkenness, drug consumption, gambling, leaving partner, imprisoned, polygamy, domestic violence. The majority couses of divorces are domestic violents and leaning parteners.